RANCANG BANGUN SISTEM MONITORING ARUS BOCOR ISOLATOR BERBASIS PLC - MUHARAM, FAJRI; WALUYO (e-Proceeding FTI, 2024)
The insulator leakage current monitoring system has an important role in maintaining the integrity of electrical insulators and preventing potential insulation failures that can cause interference with the electrical system. In this effort, this research aims to design and develop an insulator leakage current monitoring system that uses PLC. In the design stage, a system requirements analysis is carried out which includes the selection of leakage current sensors and other supporting components. PLC was chosen as the main brain of the system due to its flexibility in controlling and monitoring electronic devices. The system is designed to detect insulator leakage current with high accuracy and provide quick responses in emergency situations. During the experiment, the average value is obtained for normal, medium, and over voltage limitations of insulator leakage current. Where the limit when normal < 1.4, medium 1.4 - 1.69, and over voltage leakage current insulator > 1.69 is determined when high humidity and low temperature. Keywords: Leakage Current Monitoring, Insulator, PLC, Current Sensor, Electrical Safety. ABSTRAK Sistem monitoring arus bocor isolator memiliki peran penting dalam menjaga integritas isolator listrik serta mencegah potensi kegagalan isolasi yang dapat mengakibatkan gangguan pada sistem kelistrikan. Dalam upaya ini, penelitian ini bertujuan untuk merancang dan mengembangkan sistem monitoring arus bocor isolator yang menggunakan PLC. Pada tahap perancangan, dilakukan analisis kebutuhan sistem yang mencakup pemilihan sensor arus bocor dan komponen pendukung lainnya. PLC dipilih sebagai otak utama sistem karena fleksibilitasnya dalam mengontrol dan memonitor perangkat elektronik. Sistem dirancang untuk mendeteksi arus bocor isolator dengan akurasi tinggi dan memberikan tanggapan cepat dalam situasi darurat. Pada saat percobaan didapat nilai rata-rata untuk batasan normal, medium, dan saat over voltage arus bocor isolator. Dimana batasan saat normal <1,4, medium 1,4 – 1,69, dan over voltage arus bocor isolator >1,69 ditentukan ketika kelembaban tinggi dan suhu rendah. Kata kunci: Monitoring Arus Bocor, Isolator, PLC, Sensor Arus, Keamanan Kelistrikan.